2013
DOI: 10.1371/journal.pone.0075254
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Interleukin-19 Activity Ameliorates Esophageal Squamous Cell Carcinoma Progression

Abstract: BackgroundIL-19 is expressed in esophageal squamous cell carcinoma (SCC), but its biological effect on esophageal cancer remains unclear. We determined the correlation between IL-19 expression levels and clinicopathological variables and explored the effects of IL-19 on the esophageal SCC in vivo and in vitro. Methodology/Principal FindingsWe determined the expression levels of esophageal SCC tissues from 60 patients using immunohistochemistry. We examined the effects of IL-19 on intracellular signaling, cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…IL19 and IL24 [also known as melanoma differentiation-associated antigen 7 (MDA-7)] are members of the interleukin 10 (IL10) family of cytokines, which are involved in infectious and inflammatory diseases [5761]. ESCC patients with advanced tumor stage showed increased levels of IL19 [62], and we observed higher IL19 gene expression in the NMBA-treated rat esophagus in the current study. In addition, BRBs significantly decreased levels of IL19 gene expression (Fig.…”
Section: Resultssupporting
confidence: 54%
“…IL19 and IL24 [also known as melanoma differentiation-associated antigen 7 (MDA-7)] are members of the interleukin 10 (IL10) family of cytokines, which are involved in infectious and inflammatory diseases [5761]. ESCC patients with advanced tumor stage showed increased levels of IL19 [62], and we observed higher IL19 gene expression in the NMBA-treated rat esophagus in the current study. In addition, BRBs significantly decreased levels of IL19 gene expression (Fig.…”
Section: Resultssupporting
confidence: 54%
“…7E has previously shown specificity and neutralization activity in vitro and in vivo . 51D not only showed specificity against the extracellular domain of human (h)IL‐20R1, but also cross‐reacted with mouse (m)IL‐20R1 and rat (r)IL‐20R1 (Supporting Fig. 3).…”
Section: Resultsmentioning
confidence: 86%
“…These factors mediate activation of TGF-β, cyclin B1, matrix metalloproteinase-1 and CXCR4, all related to the proliferation and metastasis of cancer cells. In vivo studies have shown that anti-IL-19 antibody can significantly inhibit the growth of EC [ 78 ].
Fig.
…”
Section: Cytokine/chemokine Expression In Esophageal Cancermentioning
confidence: 99%